Fresh osteochondral allotransplants: Outcomes, failures and future developments. Issue 7 (July 2017) - Tschon, M.; Veronesi, F.; Giannini, S.; Fini, M.
Abstract: Osteochondral allografts are used to treat many different conditions as acute traumatic large-sized lesions, degenerative osteoarthritis, osteochondritis dissecans, avascular necrosis or in case of failure of previous procedures particularly in young patients for whom primary prosthesis is not desirable. Fresh allografts present the advantage of having mature viable hyaline cartilage, not causing donor morbidity, allowing the restoration of even large defects in a single surgical session. Conversely, they could account for risks of disease transmission, immunologic reactions, and for limited availability. The present review aimed to analyze published studies of the last decade in which patients received fresh osteochondral allografts by dividing them for knee or ankle regenerative purposes. We wish to report the observed failure rates and particularly to collect any other reported side effect or outcome for identifying major problems and limits linked to the procedure and for delineating possible future researches and approaches. The overall success rates resulted ranging from 5.3% to 48.3% in the ankle at a mean follow up of 3.3 years and from 0% to 85.7% in the knee at a mean follow up of 7.1 years. Among other outcomes, occurrence or progression of arthritis, osteolysis, graft instability, fractures, nonunions, edema and infections were recorded. Overall, the lack of well designed randomized and controlled clinical trials, of immunological determination of the anti-donor antibodies development and of local and systemic biomarkers to detect reaction to the graft seems to be the major drawback. Improvements in these limiting factors might be desirable in order to enhance the clinical scenario of a well-established and successful procedure to give, especially for young patients, a real regeneration of the joint.